Kontribusi e-comerce dalam meningkatkan omzet penjualan pada usaha mikro di Kecamatan Besuki - Farhana; Muhammad Anasrullhoh (Program Studi Akuntansi IKOPIN, 2022)
The purpose of this study was to determine the contribution of e-commerce in increasing sales turnover in micro-enterprises. The object of research is micro business actors in Besuki sub-district. The research problem formulation is: how is the influence of e-commerce on the sales turnover of micro businesses in Besuki sub-district. The approach taken by researchers is a qualitative approach, by looking for valid data, researchers conduct interviews and documentation straight to the field. Researchers examined the microenterprises as many as 6 people..